Etiology and Use of the "Hanging Drop" Technique: A Review. (15th April 2014) - Todorov, Ludmil; VadeBoncouer, Timothy
Abstract : Background . The hanging drop (HD) technique presumably relies on the presence of subatmospheric epidural pressure. It is not clear whether this negative pressure is intrinsic or an artifact and how it is affected by body position. There are few data to indicate how often HD is currently being used. Methods . We identified studies that measured subatmospheric pressures and looked at the effect of the sitting position. We also looked at the technique used for cervical and thoracic epidural anesthesia in the last 10 years. Results . Intrinsic subatmospheric pressures were measured in the thoracic and cervical spine. Three trials studied the effect of body position, indicating a higher incidence of subatmospheric pressures when sitting. The results show lower epidural pressure (−10.7 mmHg) with the sitting position. 28.8% of trials of cervical and thoracic epidural anesthesia that documented the technique used, utilized the HD technique. When adjusting for possible bias, the rate of HD use can be as low as 11.7%. Conclusions . Intrinsic negative pressure might be present in the cervical and thoracic epidural space. This effect is more pronounced when sitting. This position might be preferable when using HD. Future studies are needed to compare it with the loss of resistance technique.